Wireless sensor networks : architecture, applications, advancements - Vijayalakshmi, S. R.; Muruganand, S. (Mercury Learning and Information, 2018)
An essential guide for anyone interested in wireless communications for sensor networks, home networking, or device hacking, this book covers a large number of topics encountered in the architecture, application, and recent advancements of a wireless sensor network. --